2016
DOI: 10.1128/iai.01088-15
|View full text |Cite
|
Sign up to set email alerts
|

AraC-Type Regulator Rsp Adapts Staphylococcus aureus Gene Expression to Acute Infection

Abstract: cStaphylococcus aureus is an important human pathogen that can cause two categories of severe infections. Acute infections are characterized by pronounced toxin production, while chronic infections often involve biofilm formation. However, it is poorly understood how S. aureus controls the expression of genes associated with acute versus biofilm-associated virulence. We here identified an AraC-type transcriptional regulator, Rsp, that promotes the production of key toxins while repressing major biofilm-associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
35
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 47 publications
3
35
1
Order By: Relevance
“…The attenuated toxicity phenotype was not noted in isolates from skin and soft tissue infection (17), suggesting that such attenuated toxicity and intracellular survival may be particularly important in bloodstream infection, as opposed to other forms of infection, such as skin and soft tissue infection. Our findings that rsp contributed to lethality in pulmonary disease is also supported by a recent study of cutaneous S. aureus disease (54). In both models, toxins have been shown to be key mediators of disease (13,55).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The attenuated toxicity phenotype was not noted in isolates from skin and soft tissue infection (17), suggesting that such attenuated toxicity and intracellular survival may be particularly important in bloodstream infection, as opposed to other forms of infection, such as skin and soft tissue infection. Our findings that rsp contributed to lethality in pulmonary disease is also supported by a recent study of cutaneous S. aureus disease (54). In both models, toxins have been shown to be key mediators of disease (13,55).…”
Section: Discussionsupporting
confidence: 75%
“…Some of the Rsp effects are mediated by SSR42, because SSR42-dependent production of the Rsp targets, α-toxin, has been demonstrated (45). Synergy of SSR42-mediated effects with direct effects of Rsp itself, such the recently demonstrated binding of Rsp to the agr promoter, may also occur (54).…”
mentioning
confidence: 99%
“…We previously identified repressor of surface proteins (Rsp) as a global regulator of S. aureus hemolysis, cytotoxicity, and virulence and found that Rsp is required for transcription of SSR42, which is located directly upstream of Rsp in an antiparallel orientation (36). Loss of hemolysis has been described for mutants of rsp (36,49,51), and functional Rsp is a requirement for transcription of SSR42 (36). SSR42 is essential for wild-type hemolysis in S. aureus (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…One IS 256 insertion occurred 521-bp upstream of rsp (the gene for the AraC family transcriptional regulator [ 72 ]), suggesting an influence on the regulation system for virulence genes. In order to gain a more precise understanding of the gene expression and potential virulence of Russia ST8-IVc (OC8), further investigations are needed.…”
Section: Discussionmentioning
confidence: 99%